Notes on the new growth economics - Luyo Kuong, Jaime (2007)
In this paper we briefly review the Theory of Endogenous Economic Growth (ECG), based on the analysis of the precursor contribution of Paul Romer and other important researchers who have continued the development of this new current of thought that surpassed the stagnation suffered by the Theory of Economic Growth and made it possible for it to acquire new importance from the last decade.